Anterior Impingement Syndrome of the Ankle Caused by Osteoid Osteoma in the Talar Neck Treated with Arthroscopy and 3D C-Arm-Based Imaging. (28th March 2017) - Ikegami, Masachika; Matsumoto, Takumi; Chang, Song Ho; Kobayashi, Hiroshi; Shinoda, Yusuke; Tanaka, Sakae
Abstract : Osteoid osteoma in periarticular lesions tends to have an unusual presentation that likely leads to a delayed or missed diagnosis compared with a typical osteoid osteoma in the metaphysis or diaphysis of the long bone. In cases that are unresponsive to conservative treatment, surgical interventions including en bloc resection, computed tomography-guided percutaneous treatment, and arthroscopic resection have been performed; however, these methods frequently result in inadequate tumor resection and recurrence. Here we present a case of a 16-year-old girl with osteoid osteoma in the talar neck presenting as anterior impingement syndrome due to marked synovitis in the ankle joint which was successfully treated without complications by arthroscopic synovectomy and tumor resection followed by intraoperative 3D C-arm-based imaging confirming complete tumor lesion removal. Her pain was relieved immediately after the surgery, and there was no recurrence at 12 months of follow-up. This is the first case report of the surgical treatment of the osteoid osteoma in the talar neck with the combination methods of arthroscopy and 3D C-arm-based imaging.